Pengembangan Media Pembelajaran Augmented Reality Pada Mata Pelajaran Instalasi Motor Listrik - Chindy Febyola; Aswardi Aswardi (Jurnal Pendidikan Teknik Elektro, 2021)
Teachers are expected to provide media in debriefing pupils to meet the present industrial revolution 4.0, one of which is by leveraging technology and automation in the delivery of learning. As a result, media development as a support in the teaching and learning process is required. In class XI TITL at SMKN 5 Padang, this study intends to provide a legitimate and practical Augmented Reality learning media on the subject of electric motor installation. The research method used in this study was research and development using a 4D model. The participants in this study were students in class XI TITL 1 at SMKN 5 Padang. The validation of AR learning media carried out by the validator team in the media area was carried out by two validators who were Lecturers of Electrical Engineering and were certified legitimate, according to the study's findings. The authenticity of the material field was then tested and pronounced genuine by two teachers in charge of the subject of electric motor installation at SMKN 5 Padang. The practicality test, which was done online and offline on 32 students in class XI TITL 1 SMKN 5 Padang, was pronounced Very Practical. The effectiveness test, which was carried out on 32 students from class XI TITL 1 SMKN 5 Padang and consisted of working on 20 questions, revealed that the media used was deemed to be very effective.